PRIVATE FINANCE INITIATIVE (PFI) IN MALAYSIA: THE NEED FOR AND ISSUES RELATED TO THE PUBLIC SECTOR COMPARATOR (PSC) - Ismail, Suhaiza; Rashid, Khairuddin Abdul (Jurnal Akuntansi dan Keuangan Indonesia, 2007)
The Concept of Private Finance Initiative (PFI) or Public Private Partnership (PPP) has been internationally implemented over the last two decades. In Malaysia, eventhough the involvement of the private sector in assisting with the provision of public services and facilities is not new, only recently under the Ninth Malaysia Plan the government officially announced the implementation of projects using PFI scheme in order to promote greater involvement of the private sector in delivering public services (Ninth Malaysia Plan, 2006). Consequently, a series of PFI projects is now being implemented including some already under construction. However, little is known on the real nature of the Malaysian PFI. One of the aspects considered critical in the implementation of a PFI project is the need for a public sector comparator (PSC) to demonstrate that the project can achieve value for money through comparing the public sector comparator (PSC) with the bid or bids submitted by the private sector. The study being reported herein focuses on the concept of PFI as practiced in Malaysia and the construction of a PSC. Given that under the Malaysian PFI, the PSC is yet to be established there is an urgent need for one to be constructed. In addition, critical issues concerning the transfer of risks and the determination of discount rate are also discussed. The study combines literature review on PFI and interviews with civil servants involved in the implementation of PFI in Malaysia.